Answer:
y = 2/3x + 19/3
Step-by-step explanation:
First, this is your current equation: y = 2/3x + b. Plug in your point to the equation, it should look like this: 5 = 2/3(-2) + b. 2/3 times -2 equals -4/3. So, this is what your equation should look like: 5 = -4/3 + b. Add 4/3 to both sides of the equation to get 19/3 = b. Go back to your original equation and plug 19/3 to b. This is your final equation: y = 2/3x + 19/3. Hope this helped!
Answer:
- as written: c = P - a - b - d/4
- with parentheses: c = 4P - a - b - d
Step-by-step explanation:
The meaning of the given expression is ...
P = a + b + c + (d/4)
To solve for c, subtract all the terms on the right side not containing c.
P -(a + b + (d/4)) = c
c = P - a - b - (d/4)
_____
In such equations, parentheses are commonly missing. If that is the case here, then first we undo the division by 4, then we subtract the "not c" terms.
P = (a + b + c + d)/4 . . . . maybe what you meant
4P = a + b + c + d . . . . . . multiply by 4
4P - (a +b +d) = c
c = 4P -a -b -d
? ?? Hi so that doesn’t make sense